Loss Aversion and Regulatory Focus Effects in the Absence of Numbers: Qualitatively Framing Equivalent Messages on Food Labels - Katie M. Abrams (Journal of Applied Communications, 2015)
Examining effects of qualitatively framing information as nonloss and gain is important because not all messages can be communicated quantitatively to consumers. This is especially the case with many food labels addressing farming methods. Research on loss aversion cognitive bias has shown people react more strongly to messages framed negatively (loss/nonloss) than equivalent information framed positively (nongain/gain). A few studies, however, have shown an opposite reaction when comparing equivalent nonloss- to gain-framed information and offered regulatory focus theory as an explanation. Most studies have relied on quantitative descriptors to frame information as gains or nonlosses, but are the cognitive biases explained by loss aversion or regulatory focus still powerful using qualitatively framed information? The purpose of this study was to compare effects of qualitatively framed gain and nonloss messages within food labels on people’s attitudes. Six-hundred-sixty subjects were assigned randomly to one of two treatment groups: nonloss- or gain-framed information about environmental impact and animal welfare on a package of chicken or a control group. Results showed no difference between the frames in the effect on subjects’ attitudes toward the product. Marketers and others crafting persuasive messages who attempt to use nonloss or gain framing of information to appeal to consumers’ cognitive biases may be compromising their efforts without using numbers or quantifiable information.
Keywords: Framing effects; food labels; cognitive biases; loss aversion; regulatory focus